Assessing native speaker modeling on social media: Effects on student speaking proficiency - Kamal, Syifa Fuadatul; Sufyan, Agus; Hamid, Farida (Institut Agama Islam Negeri Palopo, 2024)
EFL students in Indonesia still discovered some problems in speaking, such as limited time in classroom practice, lack of confidence, and need for innovative learning media. Addressing this problem, this study investigated whether implementing native speakers’ modeling on social media as learning media affects students’ speaking skills. As we live in the existence of digital lives, social media has become one of the popular digital platforms; therefore, we can advance social media to assist students and teachers in classroom teaching and learning. Furthermore, social media nowadays are viral and used mainly by students, so it would not be complicated to integrate social media into a classroom activity. This study employed a quantitative method using a quasi-experimental research design that involved 58 tenth-grade students of one senior high school selected toward a purposive sampling allocated into experimental and control classes. The oral test of describing people served as a pre-test and a post-test. The t-test was employed to analyze the data. The result showed a higher score improvement in students’ speaking in the experimental class. In addition, the students were enthusiastic when the treatment was conducted. This finding means English native speakers' modeling on social media potentially affected students' speaking skills in describing people.